Developing a Therapeutic Serious Game Based on Play Therapy to Intervene Verbal and Non‑Verbal Bullying Victims: An Experimental Study in School Students - Dini Nur Saniyah; Almira Maharani; Andi Renny Nuraeni; Dewi Andrianisari; Almah Fitriah; Anugrah Azis (Jurusan Teknik Informatika dan Komputer, 2024)
This study aimed to develop and evaluate a therapeutic serious game integrating play therapy principles to improve emotional well-being, enhance coping skills, and reduce bullying-related distress among school-aged children. While prior research has focused on preventive serious games, interventions addressing the therapeutic needs of bullying victims remain limited. A randomized pretest–posttest experimental design was employed with 60 participants (aged 10–14 years) from two schools in Makassar, Indonesia. Participants were randomly assigned to an intervention group (n = 30) receiving the therapeutic serious game over four weeks or a control group (n = 30) receiving routine school support. Measures included the Bullying Victimization Scale, Emotional Well-Being Questionnaire, and Coping Skills Inventory for Children. Statistical analyses included paired-sample t-tests, independent t-tests, and ANCOVA to compare pre-post changes and between-group differences. The intervention group demonstrated significant improvements in emotional well-being (Δ = +15.6, p < 0.001), enhanced coping strategies (Δ = +13.2, p < 0.001), and reduced bullying-related distress (Δ = -15.5, p < 0.001) compared to the control group. Effect sizes were large, indicating strong therapeutic impact. The control group showed negligible changes. The findings confirm that therapeutic serious games can effectively support victims of verbal and non-verbal bullying by combining emotional expression, skill rehearsal, and scenario-based practice in an engaging digital format. This approach provides a scalable and evidence-based alternative to traditional play therapy, with potential integration into school counseling programs. Future research should examine long-term effects and cross-cultural adaptations.